Olfactory dysfunction after autoimmune encephalitis depending on the antibody type and limbic MRI pathologies - Hänsel, Martin; Schmitz-Peiffer, Henning; Hähner, Antje; Reichmann, Heinz; Schneider, Hauke (Frontiers in Neurology, 2023)
Objective Patients’ olfactory function after autoimmune encephalitis (AE) involving limbic structures may be impaired. This study aimed to characterize olfactory function in patients after autoimmune encephalitides. Methods A case–control study was performed including 11 AE patients with antibodies against NMDAR (n = 4), GAD (n = 3), VGKC (n = 3) and antibody-negative AE (n = 1) and a control group of 12 patients with pneumococcal meningo-encephalitis (PC). In subgroup analyses, AE patients with and without NMDAR-antibodies were compared. Olfactory function was assessed using the Sniffin Sticks test and the resulting TDI-score (threshold, discrimination, identification). Involvement of limbic structures was evaluated on imaging data (MRI). Statistical analyses were performed to test for correlations of TDI-score and MRI results. Results The overall olfactory function of the AE-group and the PC-group was comparable (mean TDI 32.0 [CI 27.3–36.7], 32.3 [CI 28.5–36.0)]. The proportions of hyposmic patients were similar compared to the general population. However, AE patients of the non-NMDAR group had significantly lower TDI-scores (28.9 ± 6,8) than NMDAR patients (37.4 ± 3.5) (p = 0.046) and a significantly lower discrimination capability than the NMDAR patients (9.9 ± 2.0 vs. 14.5 ± 0.6) (p = 0.002). The non-NMDAR patients had significantly more limbic MRI pathologies (6/7) compared to the NMDAR patients (0/4) (p = 0.015). Furthermore, a correlation between limbic MRI pathologies and worse capability of smelling discrimination was found (p = 0.016, r = −0.704, n = 11). Conclusion Our results indicate that patients with NMDAR autoimmune encephalitis have normal long term olfactory function. However, patients with non-NMDAR autoimmune encephalitis appear to have a persistently impaired olfactory function, probably mediated by encephalitic damage to limbic structures.